Tradiciones de resistencia y lucha : un análisis sobre el surgimiento y la permanencia de las guerrillas en Colombia (2010)
ABSTRACT: Based on the cultural perspective this article is looking to expand the explanatory framework of a fact that has become paradigmatic in the Colombian context: the long duration of the guerrilla warfare and, particularly, of the Army of National Liberation (ELN), that it has maintained itself, after 45 years, like a project of an armed fight. In that exploration, historic elements of the political tradition and of the Colombian conflict are being discussed, as well as the forms of resistance of the subordinate sectors, that constitute part of the accumulated symbolic and of the political memory that activates itself before new joints. The roots of this tradition are tracked in the partisan identities and in the sense of “doing justice”, in the formation of a warlike tradition as a privileged form of resolution of the conflicts and in the political learning that favors itself in the current alternatives or “margins” of the liberal party.